Identificación de amenazas, estrategias de manejo y conservación de los servicios ecosistémicos en Subcuenca “La Suiza” Chiapas, México - Palacios, Byron; López, Walter; Faustino, Jorge; Günter, Sven; Tobar, Diego; Christian, Brenes (Universidad Nacional de Loja. Las Argelias (Ecuador), 2019)
The sub-basin "La Suiza" due to its geographical and political location presents a high range of generation of ecosystem services. The purpose of the study was to: Identify spatially the threats that put at risk the generation of ecosystem services, and identify possible strategies for their management and conservation in the sub-basin "La Suiza". The study found 12 threats that jeopardize the generation of ecosystem services, identifying as the main threat the topography of the terrain with slopes greater than 30 % inclination equivalent to 2825.04 hectares (46 %) of the total territory of the sub-basin "La Suiza". Likewise, it was found that there was a significant association between type of threats and types of producers the p-value of the Chi square G2 statistic is = 0,0001 lower than the significance level α = 0,05. On the other hand, it was found that the payment for environmental services (PSA) stood out as a possible strategy for the conservation of ecosystem services in the sub-basin.